New evidence of Holocene atmospheric circulation dynamics based on lake sediments from southern Sweden: A link to the Siberian High - Muschitiello, F.; Schwark, Lorenz; Wohlfarth, B.; Sturm, C.; Hammarlund, D. (Pergamon, 2013)
Oxygen (d18O) and carbon (d13C) isotope records of calcitic carbonate components (Chara sp. algal encrustations and Bithynia tentaculata gastropod opercula) from a lake-sediment succession on the Baltic Sea island of Gotland, south-eastern Sweden, have been obtained to investigate regional climate dynamics during the Holocene. The hydrological sensitivity of the small lake, particularly in terms of spring snowmelt contribution to the local water budget, provides a means of tracing past changes in the influence of snow-bearing easterly winds across the Baltic Sea Proper, which signifies the wintertime strength of the Siberian High. Repeated episodic depletions in 18O at the centennial scale correlate with events of increased potassium concentration in the GISP2 ice-core record from Greenland, which indicates a coupling to large-scale fluctuations in atmospheric circulation patterns. A corresponding correlation with simultaneous depletions in 13C suggests repeated responses of the local lake hydrology to snow-rich winters through decreasing water residence time, perhaps augmented by methanogenesis due to prolonged ice-cover seasons under the influence of an expanding Siberian High. Frequency analysis of the isotopic records reveals well-defined fluctuations at quasi-500-520-, 670-, 830- and 1430-yr periodicities, and a gradually stronger impact of Polar air outbreaks across the southern Baltic Sea region with time after ca6000cal. BP. © 2013 Elsevier Ltd.